Tropidurus hygomi e Melocactus violaceus subsp. margaritaceus: saurocoria envolvendo duas espécies ameaçadas de extinção da restinga - Silva, Tainara Lima da (2022)
Saurochory is a type of mutualistic lizard-plant interaction, which has occurred in a variety of ecosystems and in different ways, being ecologically essential for both parties. Thus, the objective of this study was to evaluate saurochory involving two endangered species, evaluating the behavior, frequency of visits, dispersion distance, and germination potential of seeds consumed by lizards in an extension of Restinga in the municipality of Pirambu – SE. Fieldwork was carried out in November and December 2020 an additional expedition in January 2022. Focal observations were carried out, totaling a sampling effort of nine hours, and the capture of the lizards for collection of fecal samples, which were used in the germination experiment, as well as the collection of fruits from the plants themselves. An experiment was conducted (January to March 2021) comparing germination with seeds collected directly from fruits and those collected from lizards’ feces, in four treatments: Seeds consumed (SC); Consumed and washed seeds (SCL); Control seeds (Scontro); and Washed seeds (SL). Tropidurus hygomi visited Melocactus violaceus subsp. margaritaceus throughout the day. There were 9 visits with consumption (mean duration of 0.56 ± 0.72 min), concentrated in the morning, and 22 visits without consumption (mean time of 4.8 ± 5.1 min) at different times of the day. Observations showed that this lizard often uses the cactus, both for fruit consumption and as a thermoregulatory site or perch to observe the environment. Of the 67 lizards captured, 53 defecated, and 37 fecal samples were obtained containing seeds (N = 218), at distances varying between 2.0 – 8.0 meters from the reproductive cactus. The results of germination tests showed that T. hygomi has a high amount of viable seeds (N = 175) of M. violaceus subsp. margaritaceus in their feces. The passage of seeds through the digestive tract of lizards remained high, with 80% of the seeds consumed germinated, with a significant difference.Tropidurus hygomi is an effective disperser of M. violaceus subsp. margaritaceus, as it ingests the seeds and eliminates them intact and viable, in addition to transporting them away from the mother plant. Thus, this mutualistic interaction is important in to guarantee the reproductive success and survival of the two species, which already suffer frequent anthropic pressures.